Agent and multi-agent systems : technology and applications : 11th KES International Conference, KES-AMSTA 2017 Vilamoura, Algarve, Portugal, June 2017 Proceedings /: technology and applications : 11th KES International Conference, KES-AMSTA 2017 Vilamoura, Algarve, Portugal, June 2017 Proceedings. (2017) - Unknown
No abstract available